Buddhist Monks and the Politics of Lanka’s Civil War: Ethnoreligious Nationalism of the Sinhala Sangha and Peacemaking in Sri Lanka, 1995–2010, by Suren Raghavan - Nichols, Michael D. (Religions of South Asia, 2021)
Buddhist Monks and the Politics of Lanka’s Civil War: Ethnoreligious Nationalism of the Sinhala Sangha and Peacemaking in Sri Lanka, 1995–2010, by Suren Raghavan. Sheffield: Equinox Press, 2016. xvii + 274 pp. £85 (hb), £26.99 (pb). ISBN 978-1-78179-078-6 (hb), ISBN 978-1-78179-574-3 (pb).